An open window: women's work in the women's press in the aftermath of the First World War. Issue 1 (2nd January 2021) - Hunter, Kathryn M.; Ward, Emma
ABSTRACT: The notion of the First World War being emancipatory for women has been, if not dismissed, then highly qualified. Understanding the postwar renegotiation of gender roles, however, is a complex task, especially in a society in which women's enfranchisement had long been secured. This article aims to contribute to debates about women's experiences of the transition from war to peace and is based on the weekly women's pages in two New Zealand newspapers for the 24 months after armistice. The columns reveal that for a time, higher education and careers were promoted to women, before such encouragement waned and more traditional roles once again dominated the columns. There was, albeit briefly, an 'open window' for women in New Zealand during which time wartime experiences and disruption of norms created an environment of emancipatory thinking.